Prevalence and Characteristics of Central Compared to Obstructive Sleep Apnea: Analyses from the Sleep Heart Health Study Cohort - Donovan, Lucas M. (Sleep, 2016)
STUDY OBJECTIVES: Determine the prevalence of central sleep apnea (CSA) in a large community-based cohort using current definitions and contrast the clinical characteristics of subjects with CSA to those with obstructive sleep apnea (OSA) and no sleep apnea. METHODS: A cross sectional analysis of baseline data from 5,804 participants of the Sleep Heart Health study was performed. Subjects meeting contemporary diagnostic criteria for CSA and Cheyne Stokes respiration (CSR) were compared to those without sleep apnea and those with OSA. Demographic data, medical comorbidities, medication use, and sleep related symptoms were compared between the groups RESULTS: The prevalences of CSA and Cheyne Stokes respiration (CSR) in this sample were 0.9 (95% confidence intervals [CI]: 0.7–1.2)% and 0.4 (95% CI: 0.3–0.6)%, respectively. Individuals with CSA were older, had lower body mass indexes (BMI), lower Epworth Sleepiness Scale scores, and were more likely to be male than individuals with obstructive sleep apnea OSA. Among those with self-reported heart failure (HF), OSA was much more common at 55.1% (95% CI: 45.6–64.6) than CSA 4.1% (95% CI: 0.3–7.9). CONCLUSIONS: This is the largest community-based study of the prevalence and characteristics of CSA to date and demonstrates a prevalence of CSA that is intermediate to those previously noted. Contrary to prior data from clinic based samples, individuals with heart failure were much more likely to have OSA than CSA. CITATION: Donovan LM, Kapur VK. Prevalence and characteristics of central compared to obstructive sleep apnea: analyses from the sleep heart health study cohort. SLEEP 2016;39(7):1353–1359.